Efficient removal and environmentally benign detoxification of Cr(VI) in aqueous solutions by Zr(IV) cross-linking chitosan magnetic microspheres. (October 2017) - Chen, Xiumei; Zhang, Wengang; Luo, Xueli; Zhao, Fan; Li, Yixuan; Li, Ronghua; Li, Zhonghong
Abstract: Zirconium(IV) cross-linking chitosan (CTS) magnetic microspheres (Fe3 O4 @Zr-CTS) as a recoverable adsorbent were synthesized through the coordination reaction between zirconium oxychloride and CTS biopolymeric matrix for efficient adsorption and simultaneous detoxification of hexavalent chromium, Cr(VI), in aqueous solutions. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) confirmed the formation of core@shell magnetite microspheres. X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared spectroscopy (FT-IR) verified the crosslinking of Zr(IV) to CTS on the microspheres. Batch Cr(VI) adsorption performances of the resultant Fe3 O4 @Zr-CTS microspheres revealed that the maximum adsorption capacity of 280.97 mg/g were achieved under pH 4.0 at 298 K. The XPS analyses indicated that 61.1% of the adsorbed Cr(VI) was reduced to Cr(III) due to the oxidization of alcoholic groups on C-6 in CTS which served as electron donors to carbonyl groups. The adsorbent showed preferential Cr(VI) adsorption with the existence of co-existing cations (K +, Na +, Cu 2+, Zn 2+, Ca 2+, Mg 2+ ) and anions (NO3 −, Cl −, SO4 2−, CO3 2− ). The adsorbent exhibited excellent reusability, lower the effluent Cr(VI) contents down to the ppb level, which satisfied the drinking water standard recommended by the World Health Organization and was a promising candidate for water purification. Highlights: Efficient removal and simultaneous detoxification of Cr(VI) by Fe3 O4 @Zr-CTS microspheres. Adsorption caused by electrostatic attraction between Zr 4+ and HCrO4 − and ligand exchange between Cl − and HCrO4 − . Oxidization of hydroxyl groups on C-6 in CTS served as electron donors for Cr(VI) detoxification. Cr(III) re-adsorbed onto the newly oxidized carboxyl groups.